An Analysis of Anxiety in Juliette Nicholss Character in Silo Series - Fadhilah, Iffatunniswah; Wuryandari, Dyah Ambar (JEdu: Journal of English Education, 2025)
Literary works are human creations that express the author's thoughts and ideas in some characters. The mental and psychological factors that people experience in real life will be closely associated with the behaviours of the author's created characters in literary works for example in the aspect of anxiety. This research aims to find out the types of anxiety found in Juliette Nichols and to find out the caused of Juliette Nichols anxiety in the TV series Silo used Sigmund Freuds theory. The researchers used descriptive qualitative method. The result of this research showed that there are 3 types of anxiety there are Reality Anxiety (24 data), Neurotic Anxiety (16 data), and Moral Anxiety (1 data). The researcher also found 4 types the causes of Juliette Nichols anxiety in the TV series Silo based on Freuds theories there is Fear (6 data), Guilt (2 data), Unresolved Conflicts (9 data), and Threats (24 data).